Maximizing Anticancer Response with MPS1 and CENPE Inhibition Alongside Apoptosis Induction - Bárbara Pinto; João P. N. Silva; Patrícia M. A. Silva; Daniel José Barbosa; Bruno Sarmento; Juliana Carvalho Tavares; Hassan Bousbaa (MDPI AG, 2023)
Antimitotic compounds, targeting key spindle assembly checkpoint (SAC) components (e.g., MPS1, Aurora kinase B, PLK1, KLP1, CENPE), are potential alternatives to microtubule-targeting antimitotic agents (e.g., paclitaxel) to circumvent resistance and side effects associated with their use. They can be classified into mitotic blockers, causing SAC-induced mitotic arrest, or mitotic drivers, pushing cells through aberrant mitosis by overriding SAC. These drugs, although advancing to clinical trials, exhibit unsatisfactory cancer treatment outcomes as monotherapy, probably due to variable cell fate responses driven by cyclin B degradation and apoptosis signal accumulation networks. We investigated the impact of inhibiting anti-apoptotic signals with the BH3-mimetic navitoclax in lung cancer cells treated with the selective CENPE inhibitor GSK923295 (mitotic blocker) or the MPS1 inhibitor BAY1217389 (mitotic driver). Our aim was to steer treated cancer cells towards cell death. BH3-mimetics, in combination with both mitotic blockers and drivers, induced substantial cell death, mainly through apoptosis, in 2D and 3D cultures. Crucially, these synergistic concentrations were less toxic to non-tumor cells. This highlights the significance of combining BH3-mimetics with antimitotics, either blockers or drivers, which have reached the clinical trial phase, to enhance their effectiveness.